Review of K. S. Shrader-Frechette's Environmental ethics - Rolston, Holmes, 1932-2025, author; Joint Publication Board of Zygon, publisher (Colorado State University. Libraries, 1982)
Shrader-Frechette has anthologized 25 selections, chosen to be good beginner's pieces. Often there are opposing articles, and the authors come from diverse fields. The selections are provocative, organized around the right themes, and easily readable. There is careful attention to the mixture of scientific and technological matters with ethical and philosophical judgments. As an introductory text in environmental ethics, this is one of the best now available.
This is an electronic version of an article published in Zygon®: Journal of Religion and Science.
Keywords: environmental ethics; growth; pesticides; nuclear power; environmental justice; self-interest; future generations